Etiology, effects and management of comorbidities in multiple sclerosis: recent advances - Marrie, Ruth Ann; Fisk, John D.; Fitzgerald, Kathryn; Kowalec, Kaarina; Maxwell, Colleen; Rotstein, Dalia; Salter, Amber; Tremlett, Helen (Frontiers in Immunology, 2023)
Comorbid conditions commonly affect people with multiple sclerosis (MS). Population-based studies indicate that people with MS have an increased incidence of ischemic heart disease, cerebrovascular disease, peripheral vascular disease, and psychiatric disorders as compared to people without MS. People with MS from underrepresented minority and immigrant groups have higher comorbidity burdens. Comorbidities exert effects throughout the disease course, from symptom onset through diagnosis to the end of life. At the individual level, comorbidity is associated with higher relapse rates, greater physical and cognitive impairments, lower health-related quality of life, and increased mortality. At the level of the health system and society, comorbidity is associated with increased health care utilization, costs and work impairment. A nascent literature suggests that MS affects outcomes from comorbidities. Comorbidity management needs to be integrated into MS care, and this would be facilitated by determining optimal models of care.